2019
DOI: 10.1111/jcpp.13101
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional posttraumatic cognitions, posttraumatic stress and depression in children and adolescents exposed to trauma: a network analysis

Abstract: Background The latest version of the International Classification of Diseases (ICD‐11) proposes a posttraumatic stress disorder (PTSD) diagnosis reduced to its core symptoms within the symptom clusters re‐experiencing, avoidance and hyperarousal. Since children and adolescents often show a variety of internalizing and externalizing symptoms in the aftermath of traumatic events, the question arises whether such a conceptualization of the PTSD diagnosis is supported in children and adolescents. Furthermore, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 40 publications
8
38
0
Order By: Relevance
“…This last finding is in line with previous research in indicating that greater avoidance predicts more severe PTSD symptoms (e.g., [ 47 ]) and with DSM-5 criteria, which distinguished these criteria from other symptoms [ 5 ]. Previous studies showed that maladaptive cognitive appraisals play an important role in the development and persistence of PTSD in children and adolescents [ 48 50 ]. The severity of B criterion symptoms was not predictive of having full PTSD vs. only PTSS in our analysis, which could imply that it is more relevant the presence of intrusion symptoms (i.e., a categorical aspect) rather than how severe these are for the final outcome (i.e., a dimensional aspect).…”
Section: Discussionmentioning
confidence: 99%
“…This last finding is in line with previous research in indicating that greater avoidance predicts more severe PTSD symptoms (e.g., [ 47 ]) and with DSM-5 criteria, which distinguished these criteria from other symptoms [ 5 ]. Previous studies showed that maladaptive cognitive appraisals play an important role in the development and persistence of PTSD in children and adolescents [ 48 50 ]. The severity of B criterion symptoms was not predictive of having full PTSD vs. only PTSS in our analysis, which could imply that it is more relevant the presence of intrusion symptoms (i.e., a categorical aspect) rather than how severe these are for the final outcome (i.e., a dimensional aspect).…”
Section: Discussionmentioning
confidence: 99%
“…Participants from these studies fell into two broad categories: individuals who currently met diagnostic criteria for full or subthreshold PTSD, and individuals who were assessed as never having met criteria for PTSD or any other DSM-5 Axis-1 disorder. As per previous studies from our research group (e.g., Chen et al, 2020), subthreshold PTSD was defined according to two commonly-used sets of criteria, adapted for DSM-5 (see McLaughlin et al, 2015). Specifically, this required the presence of one Criterion B (intrusion) symptom, plus 1) either three symptoms from across Criteria C (avoidance) and D (negative alterations in mood or cognition), or two symptoms from Criterion E (alterations in arousal and physiological reactivity); or 2) one criterion C or D symptom plus one Criterion E symptom.…”
Section: Participantsmentioning
confidence: 99%
“…We were particularly interested in whether differences in inference across aversive conditioning and extinction learning were related to individual difference in avoidance symptoms, as inappropriate avoidance behaviour is thought to be a core mechanism maintaining resistance to extinction in anxiety disorders (Arnaudova et al, 2017;Pittig et al, 2020). Following recent theoretical developments that favour modelling psychological disorders as consisting of complex associations of interacting symptoms and other psychosocial factors (Borsboom, 2017), individual differences in latent cause inference were also related to multiple psychological symptom dimensions using network analysis (Greene et al, 2018;Armour et al, 2017;Fritz et al, 2018;de Haan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Across observational and intervention research in traumatic stress, pooling individual-level data across studies for integrated analyses has demonstrated the value of re-using such data in new ways. For example, pooled data have been used to examine intervention effectiveness, improve estimates of PTSD risk prediction, and broaden network analyses of traumatic stress symptoms and trauma-related cognitions (De Haan et al, 2020;Fried et al, 2018;Mithoefer et al, 2018;Shalev et al, 2019;Stein, Davidson, Seedat, & Beebe, 2003).…”
Section: 在创伤应激研究中的数据保存 共享和重复使用mentioning
confidence: 99%